Analysis Factors Influencing Abortion Decisions Among Adolescents and Their Impact on Adolescent Health - Abelia, Rani; Qyara, Heliza; Adistia, Sanny (International Journal on Health and Medical Sciences, 2024)
This research examines the factors influencing abortion decisions among adolescents and the subsequent impact on their health. It explores key determinants such as limited access to contraception, societal stigma, cultural pressures, and legal barriers that contribute to adolescent pregnancies and influence abortion choices. The study also investigates the physical, emotional, and psychological consequences of abortion on adolescents, highlighting the importance of post-abortion care and mental health support. Findings suggest that inadequate sexual and reproductive health education, coupled with cultural and legal challenges, increases the risk of unsafe abortions and negative health outcomes. The study underscores the need for comprehensive sexual education, improved access to contraception, and policy reforms to ensure safe, legal abortion services for adolescents. Addressing societal stigma and providing emotional support are also crucial in mitigating the adverse effects of abortion on adolescent well-being. These findings have important implications for adolescent health, societal attitudes, and policy development aimed at empowering adolescents to make informed and healthy reproductive choices.